2005
DOI: 10.1007/s10886-005-3539-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Birch (Betula pendula) Shoot Secondary Chemistry due to Genotype, Environment, and Ontogeny

Abstract: Plant secondary chemistry is determined by both genetic and environmental factors, and large intraspecific variation in secondary chemistry has frequently been reported. The heritability of specific tree secondary metabolites is, however, mostly unknown. We tested the effect of plant genotype, environment, and ontogeny on the variation in shoot secondary chemistry of juvenile and mature European white birches (Betula pendula). Phenolic compounds and triterpenoids were analyzed in 30 naturally regenerated 20-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 44 publications
3
47
1
Order By: Relevance
“…The authors suggested that phenolic compounds that were likely to contribute to Melampsora medusae rust immunity were present in immature leaves. In birch, however, the main phenolic compounds were found to be the same in both mature trees and clonal plantlets of the same trees (Laitinen et al 2005), and most of the variation was explained by differences among parental trees, indicating genetic control of phenolic compounds.…”
Section: Variation In Phenolics and Resistance Due To Plantinherent Fmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors suggested that phenolic compounds that were likely to contribute to Melampsora medusae rust immunity were present in immature leaves. In birch, however, the main phenolic compounds were found to be the same in both mature trees and clonal plantlets of the same trees (Laitinen et al 2005), and most of the variation was explained by differences among parental trees, indicating genetic control of phenolic compounds.…”
Section: Variation In Phenolics and Resistance Due To Plantinherent Fmentioning
confidence: 89%
“…Marked intraspecific variations in disease resistance (Elamo et al 2000;Nagy et al 2004), as well as in phenolic content (Hakulinen et al 1999;Laitinen et al 2005;Haviola et al 2006), have been reported. For instance, the susceptibility of Norway spruce to Ceratocystis polonica has been shown to be under strong genetic control (Brignolas et al 1998;Evensen et al 2000).…”
Section: Variation In Phenolics and Resistance Due To Plantinherent Fmentioning
confidence: 99%
“…B. pendula is a predominantly sexual species, but genotypes can be multiplied by micropropagation for study purposes or plantations. The B. pendula saplings used in this study were cloned from parental trees during spring 1998 (for micropropagation protocol see Laitinen et al 2004Laitinen et al , 2005 and planted at the growing site in June 1999. The growing site (61°47ЈN, 29°21ЈE) is an abandoned cultivated Weld with a Wne sandy till soil (Laitinen et al 2005).…”
Section: Plant Materials and Study Sitementioning
confidence: 99%
“…Within-plant differences in chemical defense can occur as a result of induction (Karban and Baldwin, 1997), leaf maturation (Lindroth et al, 1987;Riipi et al, 2002), somatic mutations in meristematic tissues (Suomela and Ayres, 1994;Gill et al, 1995;Tuskan et al, 1996), and through the process of ontogenetic maturation from juvenile to adult phase (Bryant and Julkunen-Tiitto, 1995;Karban and Thaler, 1999;Erwin et al, 2001;Boege and Marquis, 2005;Laitinen et al, 2005. Within-species variation in plant chemistry can affect ecological interactions and ecosystem processes. For example, primary plant compounds such as protein and water are critical for herbivore growth and development (Awmack and Leather, 2002), and qualitative or quantitative variation in phytochemical defenses within a species also strongly influences herbivore behavior and performance (Crawley, 1983;Schultz, 1988;Shelton, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas relatively little is known about the effects of development on the chemical content of plants, many studies have found that developmentally based variation can significantly influence herbivore behavior and performance (Kearsley and Whitham, 1989;Swihart and Bryant, 2001;Lawrence et al, 2003). Studies that have measured within-year and between-year (Bryant and Julkunen-Tiitto, 1995;Erwin et al, 2001;Boege and Marquis, 2005;Laitinen et al, 2005) developmentally mediated changes in plant chemistry indicate that such changes can be significant and suggest that these chemical shifts are likely to be ecologically important.…”
Section: Introductionmentioning
confidence: 99%